Voluntary Disclosure Pada Perusahaan BUMN di Indonesia - Yogaswara Margamiharja; Dedik Nur Triyanto (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
This study aims to determine the effect of public ownership, board of commissioners, independent commissioners, and audit committee on the extent of voluntary disclosure in state-owned companies listed on the Indonesia Stock Exchange for the period 2017-2019. The research was conducted on 20 state-owned companies listed on the IDX in 2017-2019. The research data were obtained from the annual reports published by the respective companies. The research method used is panel data regression analysis. The results of the study indicate that the board of commissioners variable has a positive effect on the extent of voluntary disclosure. Other variables, namely public ownership, independent commissioners, and audit committee do not affect the extent of voluntary disclosure. This research can be used as a reference for company stakeholders to consider the number of commissionerss in considering the extent of voluntary disclosure. Keywords: Extent of voluntary disclosure, public ownership, board of commissioners, independent commissioners, audit committee.